Fungsi Badan Dakwah Islam Dalam Upaya Membentuk Kepribadian Islami Pada Peserta Didik - Wijayanti, Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
The Islamic missionary (da'wah) Agency as an Intra-School Organization is another vehicle for adding and enriching the science in the religious field that is not obtained in the classroom, due to the limited time and curriculum. Missionary agency is one of the means and alternatives in improving the science of religion and improving the quality of religion in shaping the student's personality. Islamic Missionary Agency has been instrumental in developing the function of mindset as a driving force in improving the achievement of its members and improving the quality of islmaic lessons, especially religious education. And Islamic Missionary Agency has also implemented the role of developing the soul pattern function that is closer to Allah SWT by multiplying the worship and always connect the needs of body and instinct with the rules of Allah SWT. With the formation of both patterns, the mindset and pattern of the soul will form the personality of Islamic learners in accordance with the purpose of national education.